How can the management of fitness centres be improved through corporate image and brand image? - M. Alguacil (Taylor & Francis Group, 2021)
The aim of this research is to test the role of corporate image in predicting credibility, trust, and brand recognition. In addition, it is intended to verify whether these variables can explain the attitudes and future intentions of fitness centre users to better understand their behaviour. Through an online survey, the opinions of 325 fitness centre users were collected regarding the previously mentioned variables. A structural equation model was made by means of EQS 6.4 to confirm, first, the reliability of the scales used and subsequently test the different relationships between variables. The results show the importance of corporate image as a starting point to explain future intentions. Between 78% and 91% of the variance of credibility, trust, and recognition and, consequently, up to 90% of attitudes and 62% of future intentions can be explained by the equation. Thus, managers should not only focus on the variables related to the experience or performance of the service but also attend to brand variables. This research represents a contribution to the literature on brand perception and its relationship with consumer behaviour in fitness centres, an uncommon topic in this context.